Domestic Implementation of Crimes against Humanity in Central Asia. Issue 2 (26th December 2022) - Atadjanov, Rustam
Abstract : Crimes against humanity constitute mass crimes against civilian populations and represent the so-called 'core crimes' of international criminal law. Central Asian states have so far abstained from incorporating the corpus delicti of crimes against humanity in their criminal legislation. After a short overview of the current status of crimes against humanity under international law, this article analyses the domestic legislation of five Central Asian countries: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan. It looks at current Criminal Codes to suggest how those could be strengthened by the inclusion of properly formulated crimes against humanity dispositions, taking into account the peculiarities of these national legal systems. The article also offers a brief review of possible factors which might have precluded the states in question from proper implementation. It argues in favour of such implementation, delineating its legal benefits and potential advantages for both State Parties and non-State Parties to the Rome Statute in Central Asia.